Female Sex Hormone Effects on the Vasculature: Considering the Validity of Restricting Study Inclusion to Low-Hormone Phases - Turner, Casey G.; Stanhewicz, Anna E.; Wong, Brett J. (Frontiers in Physiology, 2020)
Many studies of vascular function limit the testing of premenopausal female participants to periods when female sex hormones, either endogenous or exogenous, are at their lowest concentration. This practice, when not part of the specific research question, may limit data surrounding the predominant physiological state of premenopausal females and pose a threat to external validity. In this Perspective, we briefly review the literature on the effect of female sex hormones on vascular function and discuss when limiting experimental testing to a certain phase of the menstrual cycle or oral contraceptive use may be appropriate. The goal of this Perspective is to open a dialogue that may enhance data validity and the overall understanding of vascular function in premenopausal females.